APROPRIATION OF METAFORA IN FILM ADVERTISING “MANDIRI SECURITAS” - Handriyotopo, Handriyotopo; Lastoro, GR Lono; Gustami, SP (Seni Media Rekam ISI Surakarta, 2018)
Mandiri Securitas Advertising Film is an advertising film using the rhetoric strategy of visual communication of the kris masters as a creative approach. The theme as a basic idea for the creation of the Mandiri Securitas advertisement film seeks to understand the effort of working hard to produce details from the master's work to produce a keris blade, created with metaphorical rhetoric to represent the image of Mandiri Securitas in serving its customers whether they can work well or not by looking at each the role of the political rhetoric domain and banking rhetoric in both. The purpose of this study was to critically identify the two domain metaphorical rhetoric by looking at each role of the constituent elements of the Mandiri SecuritasÂ advertising film. This research method uses descriptive qualitative deconstruction by